Using Mobile Learning Tools in Higher Education: A UAE Case - Eppard, Jenny; Hojeij, Zeina; Ozdemir-Ayber, Pinar; Rodjan-Helder, Marlieke; Baroudi, Sandra (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Research indicates that mobile learning (ML), has the potential to transform teaching and learning. Despite its benefits, mobile learning adoption is a challenging process which requires support to facilitate its integration. The focus of this article is to investigate the factors that could affect ML acceptance. The quantitative and qualitative data collected from the surveys revealed additional information regarding the pedagogical benefits of and obstacles to mobile learning integration. Even though participants in this study reported to be late adopters of technology, they maintained that ML is useful for learning, specifically ubiquitous learning. Teachers also noted that mobile learning integration is more successful when aligned with local cultural norms. Mobile learning tools that might be culturally appropriate in one context may not always be accepted in another. Findings of this study provide several implications and recommendations for future research on mobile learning implementation. Further research could explore the development and utilization of a rubric with specific criteria for evaluating mobile learning applictations.